X-Raying the Positive-Negative Effects of Social Media Networks on Young Persons: The Mediating Role of Media House in Nigeria - Edih O. University; Umuze N. Anthonia; Igemohia Fidelis; University E. Ebitare (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The study x-rayed the positive-negative effects of social media networks: the mediating role of media house in Nigeria. It was organized into six sections; introduction, positive effects, negative effects, the Nigerian experience, the mediating role of the media and conclusion. The main objective was to dissect the intricacies (benefits and abuses or harms) surrounding the use of the social media and to find measures of curtailing the excesses or negative effects of the social media on young persons. The study found that young persons are glued to the social media and it will be very difficult to gag or censor its use. However, the media house has enormous task by constantly deploying sensitization, and advocacy mechanisms to abreast young people of the ills associated or interfacing with social media networks. It is therefore suggested that there should collaborations among all stakeholders; governments, media house, families, churches, mosques and educational institutions towards educating and enlightening juveniles on proper use of the social media networks.